2006
DOI: 10.1002/ejic.200600594
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Apical C–H···M Interactions in Square‐Planar Nickel(II) Complexes with Dianionic Tridentate Ligands and 2‐Phenylimidazole

Abstract: Keywords: Nickel(II) complexes / Square-planar complexes / Apical C-H···Ni interactions / X-ray structures / Theoretical calculations and sp 2 N-donor 2-phenylimidazole (phim) as the ancillary ligand have been synthesised and characterised by analytical, spectroscopic, magnetic and electrochemical methods. The solid-state structures of both complexes have been determined by X-ray crystallography. The asymmetric unit of 1 contains a single complex molecule while that of 2 contains four complex molecules with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
6
36
0
Order By: Relevance
“…In both complexes, babh 2-binds the metal centre through the two imine-N and the two deprotonated amide-O atoms forming three five-membered chelate rings and an N 2 O 2 squareplane around the metal centre. Table 2) are similar to the bond lengths observed in the corresponding bivalent metal ion complex having the same coordinating atoms [18][19][20][21][22][23][24][25][26][27][28]. In the latter complex, the apical Cu-O (methanol) bond length is relatively longer than the equatorial bond lengths.…”
Section: Spectroscopic Featuressupporting
confidence: 74%
See 2 more Smart Citations
“…In both complexes, babh 2-binds the metal centre through the two imine-N and the two deprotonated amide-O atoms forming three five-membered chelate rings and an N 2 O 2 squareplane around the metal centre. Table 2) are similar to the bond lengths observed in the corresponding bivalent metal ion complex having the same coordinating atoms [18][19][20][21][22][23][24][25][26][27][28]. In the latter complex, the apical Cu-O (methanol) bond length is relatively longer than the equatorial bond lengths.…”
Section: Spectroscopic Featuressupporting
confidence: 74%
“…These two bands are not observed in the spectra of the complexes. Absence of these bands is consistent with the iminolate form [18][19][20][21][22][23][24][25][26][27][28]37] Electronic spectra of the complexes were recorded in methanol solution. Both complexes display a strong band in the visible region.…”
Section: Spectroscopic Featuresmentioning
confidence: 97%
See 1 more Smart Citation
“…At the type 1 Cu center of these proteins a methyl group from the alkyl side chain is located above the Cu plane with the CuÁ Á ÁC distance of 3.51-3.76 Å [12,13,[16][17][18][19], and in none of the cases is the alkyl group considered as a ligand. Axial interactions between an electron-rich metal center (M) and the hydrogen atom of C-H bonds were reported earlier by Maitlis et al for a Pd(II) complex [20], and MÁ Á ÁH-X interactions (X = C, N, O) have been observed in various planar complexes of d 8 metal ions [21][22][23][24][25][26][27][28]. A similar axial contact was also reported for a Cu(II) complex with a hydrogen atom from a pendent aromatic ring above the coordination plane [29].…”
Section: Introductionmentioning
confidence: 79%
“…Complexes that contain anagostic M-H-C interactions are typically associated with d 8 transition metals centers that are square planar prior to the interaction, as illustrated by a variety of rhodium(I) phosphinate complexes synthesized by Bergman and coworkers (43). m Crabtree, Eisenstein, and coworkers (44) examined the structural characteristics of complexes that featured M-H-N and M-H-C interactions in otherwise square planar d 8 complexes and concluded that although the former are appropriately described as hydrogen bonds because the M⅐⅐⅐H-N bonds are close to the linear, the situation is ambiguous for the M-H-C interactions.…”
Section: Agostic and Anagostic Interactionsmentioning
confidence: 99%